Measures of effective population size in sea otters reveal special considerations for wide‐ranging species. (17th May 2018) - Gagne, Roderick B.; Tinker, M. Timothy; Gustafson, Kyle D.; Ralls, Katherine; Larson, Shawn; Tarjan, L. Max; Miller, Melissa A.; Ernest, Holly B.
Abstract: Conservation genetic techniques and considerations of the evolutionary potential of a species are increasingly being applied to species conservation. For example, effective population size ( N e ) estimates are useful for determining the conservation status of species, yet accurate estimates of current N e remain difficult to obtain. The effective population size can contribute to setting federal delisting criteria, as was done for the southern sea otter ( Enhydra lutris nereis ). After being hunted to near extinction during the North Pacific fur trade, the southern sea otter has recovered over part of its former range, but remains at relatively low numbers, making it desirable to obtain accurate and consistent estimates of N e . Although theoretical papers have compared the validity of several methods, comparisons of estimators using empirical data in applied conservation settings are limited. We combined thirteen years of demographic and genetic data from 1, 006 sea otters to assess multiple N e estimators, as well as temporal trends in genetic diversity and population genetic structure. Genetic diversity was low and did not increase over time. There was no evidence for distinct genetic units, but some evidence for genetic isolation by distance. In particular, estimates of N e based on demographic data were much larger than genetic estimates when computed for the entire range of the population, but were similar at smaller spatial scales. The discrepancy between estimates at large spatial scales could be driven by cryptic population structure and/or individual differences in reproductive success. We recommend the development of new delisting criteria for the southern sea otter. We advise the use of multiple estimates of N e for other wide‐ranging species, species with overlapping generations, or with sex‐biased dispersal, as well as the development of improved metrics of genetic assessments of populations.